Comparing the Push–Pull Technique to Pressure Bag for Administration of Blood Products: A Prospective Nonblinded Observation Simulation-based Study (CoPP toP Study) - Aaron Jacob Grossberg; Daniel A. Fowl; Brian T. Merritt; George M. Nackley; Jude A. Polit-Moran; Chelsea L. Savona; Sagar C. Galwankar (Journal of Emergencies, Trauma and Shock)
Introduction: Shock is defined as inadequate delivery of oxygen to meet the tissue’s demands. There are four main types of shock: cardiogenic, obstructive, distributive, and hypovolemic. Hypovolemic shock causes include hemorrhage, dehydration, and burns. Blood loss results in inadequate oxygen delivery to the cells resulting in tissue death if not reversed. Rapid infusers allow for the rapid administration of blood and crystalloid products to patients in shock; however, many community emergency departments do not have these devices. The aim of our study is to determine the fastest way to administer blood when the viscosity of the fluid is taken into consideration in a simulated setting. Methods: Volunteers were assigned to one of two arms: either the push–pull technique or pressure bag technique. The push–pull technique involved using a 50 cc syringe connected to a 3-way stop-cock to withdraw and infuse the fluid. The pressure bag technique involved pumping a pressure bag up to the maximum to infuse the fluids. The speed of infusing 250 mL of intravenous fluids was recorded. The time for the subjects to collect the materials throughout the emergency department was also recorded. Results: A total of three trials were conducted. On average, the push–pull technique took 228 s and the pressure bag technique took 340 s. The push–pull technique took an average of 112 s less than the pressure bag technique. Subjects took 62 s to find the materials for the pressure bag technique. It took 133 s to find the material for the push–pull technique. Conclusion: This prospective nonblinded observation simulation-based study demonstrated that the push–pull technique was significantly faster than the pressure bag technique.